1996
DOI: 10.1073/pnas.93.25.14857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein calorie malnutrition on tuberculosis in mice

Abstract: Infectious diseases and malnutrition represent major burdens aff licting millions of people in developing countries. Both conditions affect individuals in industrialized nations, particularly the aged, the HIV-infected, and people with chronic diseases. While malnutrition is known to induce a state of immunodeficiency, the mechanisms responsible for compromised antimicrobial resistance in malnourished hosts remain obscure. In the present study, mice fed a 2% protein diet and developing protein calorie malnutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 26 publications
6
104
0
2
Order By: Relevance
“…This last assumption is enough to reproduce the patterns of (high) incidence of active-TB over the past 150 years! Malnutrition (Chan et al 1996, Raloff 1996 and other factors that weaken the body immune's response are known to increase the risk of developing active-TB. Hence, it is not a stretch to assume that increases in the average standard of living actually streghthens the average population immune-response to diseases like TB.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…This last assumption is enough to reproduce the patterns of (high) incidence of active-TB over the past 150 years! Malnutrition (Chan et al 1996, Raloff 1996 and other factors that weaken the body immune's response are known to increase the risk of developing active-TB. Hence, it is not a stretch to assume that increases in the average standard of living actually streghthens the average population immune-response to diseases like TB.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…Much work in this area has focused on the association of protein calorie malnutrition (PCM) and reduced immune function. Chan et al (1996) demonstrated that mice receiving a reduced protein diet (2%) rapidly succumbed to tuberculosis accompanied by a reduced expression of interferon γ, tumor necrosis factor ά , and nitric oxide synthase in the lungs. These cytokines, as well as interleukin-1 (IL1), interleukin-4 (IL4), and transforming growth factor β are critical to the production of nitrous oxides and other reactive nitrogen intermediates, which are used by phagocytes to kill pathogens (Plouffe et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In previous experiments, there have been variable inflammatory immune responses to malnutrition. Decreased plasma TNFa production has been reported in rodent models of protein-energy malnutrition (Chan et al 1996, Schaffer et al 1997, Anstead et al 2001, but increased plasma IL6 concentration has been observed in malnourished patients (Malave et al 1998, Johann-Liang et al 2000, de Martino et al 2000. In addition, maternal dietary protein restriction decreased NO synthase (NOS) in endometrium and placenta of pigs during early gestation (Wu et al 1998).…”
Section: Discussionmentioning
confidence: 99%